2009
DOI: 10.1038/sj.bjc.6605369
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia, Snail and incomplete epithelial–mesenchymal transition in breast cancer

Abstract: BACKGROUND: Hypoxia is an element of the tumour microenvironment that impacts upon numerous cellular factors linked to clinical aggressiveness in cancer. One such factor, Snail, a master regulator of the epithelial -mesenchymal transition (EMT), has been implicated in key tumour biological processes such as invasion and metastasis. In this study we set out to investigate regulation of EMT in hypoxia, and the importance of Snail in cell migration and clinical outcome in breast cancer. METHODS: Four breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
151
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 40 publications
18
151
0
Order By: Relevance
“…3,4 Our work demonstrated that the loss of E-cadherin itself, without a mesenchymal phenotype, may not be associated with invasive behavior, whereas tumors with a mesenchymal phenotype, regardless of E-cadherin expression, showed aggressive behavior in esophageal squamous cell carcinoma. Recently, Uchikado et al 21 reported that the patients with esophageal squamous cell carcinoma who were positive for Slug expression had deeper tumor invasion and worse prognosis in the E-cadherin preserved group.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…3,4 Our work demonstrated that the loss of E-cadherin itself, without a mesenchymal phenotype, may not be associated with invasive behavior, whereas tumors with a mesenchymal phenotype, regardless of E-cadherin expression, showed aggressive behavior in esophageal squamous cell carcinoma. Recently, Uchikado et al 21 reported that the patients with esophageal squamous cell carcinoma who were positive for Slug expression had deeper tumor invasion and worse prognosis in the E-cadherin preserved group.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, because of the dynamic and reversible nature of epithelial-mesenchymal transition, numerous advanced carcinomas that adopt some mesenchymal features retain the characteristics of well-differentiated epithelial cells. 3,4 In vivo, epithelial-mesenchymal transition phenotypes include the extremes, ranging from an epithelial phenotype to a complete mesenchymal phenotype with a variety of intermediate sub-phenotype combinations between these extremes. Examples of intermediate sub-phenotypes include the 'hybrid type' that is a mixed epithelial and mesenchymal phenotype and the 'null type' that can be defined as the loss of the epithelial phenotype without acquisition of mesenchymal phenotype.…”
mentioning
confidence: 99%
“…4B, the existence of seven possible phases (the corresponding nullclines are included in SI Appendix, Section 10): (i) monostable phenotypes-{E}, {M}, and {E/M}; (ii) coexistence of two phenotypes-{E, M}, {E, E/M}, and {E/M, M}; and (iii) coexistence of all three phenotypes-{E, E/M, M}. The richness of these identified phases can help explain experiments regarding the diverse behaviors triggered by SNAIL (34)(35)(36) in inducing EMT. According to the rate of SNAIL increase and to the details of how it is increased (e.g., by TFG-β or hypoxia, which also affect the level of ZEB), the cells will follow a different trajectory in the phase diagram and thus will go through different phenotypic transitions.…”
Section: Resultsmentioning
confidence: 99%
“…Under hypoxic conditions, a tumor microenvironment is generated and tumor cells undergo epithelial-to-mesenchymal transition (EMT) (9). During this process, tumor cells can adjust to the newly formed microenvironment and gain stem-cell characteristics that promote differentiation and proliferation of tumor cells.…”
Section: Introductionmentioning
confidence: 99%